PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MATERI SEJARAH TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP NEGERI 2 LUHAK NAN DUO SEMESTER GANJIL TAHUN AJARAN 2014/2015 - Elfitrawati, Silvi - (Pendidikan Sejarah, 2014)
The studentsâ low learning result can be caused by some factors, one of them are IPS lesson that still focus to teacher in order to they are bored, not important and does not motivate in learning. In briefly, the students do not understand the lesson at class. Giving cooperative learning model type Make A Match is hoped to improve the studentsâ activity result in IPS lesson of history material and develop the studentsâ learning result. The purpose of the research is to know the effect of using cooperative learning model in type Make A Match of history material toward studentsâ learning result at class VII SMP N 2 Luhak Nan Duo in odd semester year 2014/2015. This research is experiment research with Control Group Pretest and Posttest Design. Sample takes with random sampling that can be class VII2 as experiment class amount 26 students and VII3 as control class amount 27 students. The data collection in this research is primer data of the last score in objective test amount 29 tests. From both of sample class are chosen, then analysis by using t exam. If tcalculate > ttable. So hypothesis is accepted and otherwise. From the result of research is got tcalculate of 2.49 for all tests and 1.69 for fact test from ttable of 1.67 in free degree of 51. In briefly, tcalculate > ttable can be accepted with real score of 0.05. So, it can be concluded that giving cooperative learning model type Make A Match give positive effect in 0.05 score toward IPS lesson result of history education at class VII SMP Negeri 2 Luhak Nan Duo year 2014/2015.